The Urban Development of Milan in the Early Christian Age (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2015)
A lot of contemporary evidences describe the events that affected Milan in the early Christian age and integrate the knowledge offered by the archaeological remains and surviving monuments. Nevertheless, the redefinition in the Christian meaning of the urban landscape emerges more clearly only in the age of Ambrose, while it is very difficult to clarify the previous progress of Christianization and in particular the contribution of Constantine and his sons. They operated perhaps in the organization of the cemetery ad martyres, main suburban worship pole, but we don’t know if they have further operated in modifying the urban complex of Maximian’s age.
Keywords: Milan; urban archaeology; early Christian age; Costantin